Prospect of land grant for forestry development in Igboland, Nigeria (2015)
Forests are assets that can promote community development and improve household livelihood if sustainably managed. The foremost constraint to sustainable forest management however, is land and in Nigeria, the southeastern (SE) region which is the dominant geographical location of Igboland has the lowest forest cover and available land area for development. This paper therefore reports the prospect of land grant for forestry development activities in the region. Multi-stage sampling (involving States in the region, their LGAs, Communities and Households) was used to select 1,133 households at 40%, 30%, 20% and 10% intensities for the study. A set of structured and semistructured questionnaire was administered to households in the sampled communities. Data were analysed using descriptive statistics and multinomial regression at α0.05. The proportion of male respondent for the study was high (82.0%). They are engaged in civil service (40.0%), businesses (23.0%) and farming (16.0%). The average cost of a plot of household land is N42,076 and average monthly income was about N79,080. Consent of granting land to forestry development groups by household heads was found to be skewed towards indigenous group (32.1%) followed by NGOs (21.4%) and government forestry department (15.9%). The income of the households as well as market cost of a plot of the household land will positively influence land grant for forestry projects. Age of landowners however showed negative significant influence to land grant for forestry. The possibility of land grant to indigene groups with forestry interests could be comparatively highest in rural communities located away from urban sprawl (Coeff. = 0.092). Thus, for forestry to thrive in Igboland, it should aim at building and foster local content as well as strengthen interest through attractive incentives.